Software architecture for web Developers - Ghidersa, Mihaela Roxana (Packt Publishing, 2023)
Discover an accessible pathway to advancing your career and becoming a web architect by building a solid technical ground in software architecture About This Audiobook Follow your desired career path that leads to a lucrative job as a web architect Develop a solid technical background in software architecture using real-world practices and patterns Learn proven techniques and design considerations from an industry expert In Detail Large-scale web applications require you to write code efficiently following business and architectural considerations. They require web developers to understand the impact of their work on the system and how they can evolve the product. With this audiobook, every developer will find something to take away. This audiobook will help web developers looking to change projects or work on a new project in understanding the context of the application, along with how some design decisions or patterns fit better in their application's architecture. It acts as a guide, taking you through different levels of professional growth with a focus on best practices, coding guidelines, business considerations, and soft skills that will help you gain the knowledge to craft a career in web development. Finally, you'll work with examples and ways of applying the discussed concepts in practical situations. By the end of this book, you'll have gained valuable insights into what it means to be a web architect, as well as the impact architecture has on a web application. Audience This audiobook is for web developers who want to become web architects. Beginner-level web developers will be able to develop a strong technical background, and experienced web developers will learn techniques to become better professionals by understanding the web architect's role and the impact of efficient architecture on their projects.